Impaired noradrenaline-induced lipolysis in white fat of aP2-Ucp1 transgenic mice is associated with changes in G-protein levels - Flachs, Pavel; Novotný, Jirí; Baumruk, Filip; Bardová, Kristina; Bourová, Lenka; Miksík, Ivan; Sponarová, Jana; Svoboda, Petr; Kopecký, Jan (The Biochemical journal, 2002)
In vitro experiments suggest that stimulation of lipolysis by catecholamines in adipocytes depends on the energy status of these cells. We tested whether mitochondrial uncoupling proteins (UCPs) that control the efficiency of ATP production could affect lipolysis and noradrenaline signalling in white fat in vivo. The lipolytic effect of noradrenaline was lowered by ectopic UCP1 in white adipocytes of aP2-Ucp1 transgenic mice, overexpressing the UCP1 gene from the aP2 gene promoter, reflecting the magnitude of UCP1 expression, the impaired stimulation of cAMP levels by noradrenaline and the reduction of the ATP/ADP ratio in different fat depots. Thus only subcutaneous but not epididymal fat was affected. UCP1 also down-regulated the expression of hormone-sensitive lipase and lowered its activity, and altered the expression of trimeric G-proteins in adipocytes. The adipose tissue content of the stimulatory G-protein alpha subunit was increased while that of the inhibitory G-protein alpha subunits decreased in response to UCP1 expression. Our results support the idea that the energy status of cells, and the ATP/ADP ratio in particular, modulates the lipolytic effects of noradrenaline in adipose tissue in vivo. They also demonstrate changes at the G-protein level that tend to overcome the reduction of lipolysis when ATP level in adipocytes is low. Therefore, respiratory uncoupling may exert a broad effect on hormonal signalling in adipocytes.
Keywords: hepatocyty; adenosintrifosfát; sekvence nukleotidů; Male; AMP cyklický; Genotype; Cyclic AMP; Uncoupling Protein 1; proteiny vázající GTP; tuková tkáň; membránové proteiny; Gene Expression Regulation, Enzymologic; noradrenalin; Membrane Proteins; Norepinephrine; iontové kanály; mužské pohlaví; DNA Primers; lipasa; mitochondriální proteiny; GTP-Binding Proteins; Hepatocytes; Carrier Proteins; Ion Channels; Mitochondrial Proteins; lipolýza; Animals; Adipose Tissue; myši transgenní; uncoupling protein 1; regulace genové exprese enzymů; zvířata; Lipolysis; myši inbrední C57BL; myši; DNA primery; Adenosine Triphosphate; Mice, Inbred C57BL; genotyp; adenosindifosfát; Base Sequence; Lipase; Mice; transportní proteiny; Mice, Transgenic; Adenosine Diphosphate